Another Country, Another Time: Notes on Pascal Mercier’s Nachtzug nach Lissabon and an idea of Europe - de Medeiros, Paulo (Cadernos de Literatura Comparada, 2016)
Pascal Mercier’s best-selling novel Night Train to Lisbon and its film adapation are examined as a case study in the relations between North and South and the image of Europe. The novel is significant inasmuch as it counters hegemonic World-Literature tendencies that privilege mostly central, English or French, novels in the European context. It is argued that even though both have significant differences and the novel manages to escape simple clichéd representations of Portugal, both ultimately stage a failure to conceptualize Europe transnationally. Ultimately, the romanticized desire for a would-be more vibrant form of engagement with life and art that would characterize the South does no more than misappropriate its past.